QUALITY IMPROVEMENT OF DISQUALIFIED TIGER PRAWN (Penaeus monodon Fab.) BROODSTOCK USING DOPAMINE - Etty Riani; MOZES TOELIHERE; ICHSAN EFFENDIE; TUTI L YUSUF; SRIHADI AGUNGPRIYONO (SEAMEO BIOTROP, 2010)
Disqualified tiger prawn broodstock is the one that has undergone ablation after two breeding periodes which causes high production cost pollution of environment and difficulties in providing it continuously with enough quantity at exact time The purpose of this study is to find the proper dosage of dopamine which will give good quality for breeding of the disqualified tiger prawn because dopamine inhibits maturation so it has enough time for maturation and can be improved the eggs quality This experiment used 15 pairs the twice breeding tiger prawn which is taken from Perigi Central Java The sample were treated with difference dosage of dopamine dosage 109 108 107 106 moll and controlinjected by aquabidest The parameters were identified in this experiment are duration days for eggs maturation fecundity fertilizing rate hatching rate egg diameter and phototaxis respnnsive of the nauplii The result of this research are the of the average of duration for eggs maturation on the broodstock that were injected dopamine dosage 109 108 107 106 moll and control were 14 12 4 2 5 days Fecundity 561489 503000 384205 230850 and 150034 Fertilizing rate 898 821 560 463 and 232 Hatching rate 7953 7253 4775 1227 and 366 Diameter 029 029 029 027 and 027mm The nauplii that had produced by injected broodstock by dosage 109 108 107 have the positive phototaxis responsive while dosage 106 and control were weak Key words Disqualified dopamine dosage duration maturation fecundity fertilizing hatching diameters nauplii